2008
DOI: 10.1007/s00441-008-0616-6
|View full text |Cite
|
Sign up to set email alerts
|

The phytoestrogens daidzein and genistein enhance the insulin-stimulated sulfate uptake in articular chondrocytes

Abstract: Clinical observations have suggested a relationship between osteoarthritis and a changed estrogen metabolism in menopausal women. Phytoestrogens have been shown to ameliorate various menopausal symptoms. Proteoglycans (PG) consisting of low and high sulfated glycosaminoglycans (GAG) are the main components of articular cartilage matrix, and their synthesis is increased by insulin in growth plate cartilage. We have investigated whether GAG synthesis and sodium [35S]sulfate incorporation in female bovine articul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…Furthermore, it seems that phytoestrogen has an effect on preserving bone volume in the absence of estrogen [34,35]. Also, the phytoestrogens daidzein and genistein but not by 17β-estradiol enhance the insulin-stimulated glycosaminoglycan synthesis in articular chondrocytes [36]. Sanchez et al have shown that OA osteoblasts in monolayer increased glycosaminoglycan release from cartilage explants, whereas normal cells did not [37].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it seems that phytoestrogen has an effect on preserving bone volume in the absence of estrogen [34,35]. Also, the phytoestrogens daidzein and genistein but not by 17β-estradiol enhance the insulin-stimulated glycosaminoglycan synthesis in articular chondrocytes [36]. Sanchez et al have shown that OA osteoblasts in monolayer increased glycosaminoglycan release from cartilage explants, whereas normal cells did not [37].…”
Section: Discussionmentioning
confidence: 97%
“…5,18,19) Dong et al 20) have reported that bavachin, a phytoestrogen purified from natural herbal plants such as Psoraleae corylifoliae 21) and Piper longum, 22) has estrogen-like activity in estrogen-receptor-positive human breast adenocarcinoma MCF-7/BOS cells. Therefore, we hypothesized that bavachin may have chondroprotective effects as a result of anabolic or anti-catabolic activity in articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of phytoestrogens, especially genistein, on the extracellular cartilage matrix has been discussed in the literature, the data are not consistent. An in vitro study found that articular chondrocyte glycosaminoglycans (GAG) synthesis was significantly diminished following incubation with high doses of genistein (10 -5 -10 -4 mol/L) but that the level of sulfate npg incorporation was not affected [1] . Nevertheless, Hooshmand et al found that high doses of genistein (10 -5 -10 -4 mol/L) could suppress the increased levels of YKL-40 (a marker of cartilage glycoprotein degradation) in chondrocyte supernatant that is induced by LPS treatment [15] .…”
Section: Discussionmentioning
confidence: 99%
“…OA is a degenerative disease characterized by the loss of collagens and proteoglycans as the main structural molecules of articular cartilage [1] . Epidemiological studies have shown that the prevalence and incidence of OA increase after menopause and that OA symptoms are more severe in postmenopausal women than in men [2][3][4] , which suggests a link between OA and estrogen.…”
Section: Introductionmentioning
confidence: 99%